Iron Deficiency Leads to Chlorosis Through Impacting Chlorophyll Synthesis and Nitrogen Metabolism in Areca catechu L. - Li, Jia; Cao, Xianmei; Jia, Xiaocheng; Liu, Liyun; Cao, Haowei; Qin, Weiquan; Li, Meng (Frontiers in Plant Science, 2021)
Deficiency of certain elements can cause leaf chlorosis in Areca catechu L. trees, which causes considerable production loss. The linkage between nutrient deficiency and chlorosis phenomenon and physiological defect in A. catechu remains unclear. Here, we found that low iron supply is a determinant for chlorosis of A. catechu seedling, and excessive iron supply resulted in dark green leaves. We also observed morphological characters of A. catechu seedlings under different iron levels and compared their fresh weight, chlorophyll contents, chloroplast structures and photosynthetic activities. Results showed that iron deficiency directly caused chloroplast degeneration and reduced chlorophyll synthesis in chlorosis leaves, while excessive iron treatment can increase chlorophyll contents, chloroplasts sizes, and inflated starch granules. However, both excessive and deficient of iron decreases fresh weight and photosynthetic rate in A. catechu seedlings. Therefore, we applied transcriptomic and metabolomic approaches to understand the effect of different iron supply to A. catechu seedlings. The genes involved in nitrogen assimilation pathway, such as NR (nitrate reductase) and GOGAT (glutamate synthase), were significantly down-regulated under both iron deficiency and excessive iron. Moreover, the accumulation of organic acids and flavonoids indicated a potential way for A. catechu to endure iron deficiency. On the other hand, the up-regulation of POD-related genes was assumed to be a defense strategy against the excessive iron toxicity. Our data demonstrated that A. catechu is an iron-sensitive species, therefore the precise control of iron level is believed to be the key point for A. catechu cultivation.